Influence of Pre-germination Treatments on Germination Potentials and Seedling Vigour of Albizia zygia(D.C. Macbr.) - JA Yisau; AM Aduradola; DA Agboola; OA Jayeola (Journal of Applied Sciences and Environmental Management, 2015)
This study was carried out with the aim of providing basic information on the best pre-treatments in breaking  dormancy experienced by Albizia zygia seeds and seedling growth. 120 seeds of Albizia zigia were subjected to mechanical scarification (at three selected points namely: around the circumference, distal and micropyle   ends). 120 seeds were pre-treated with hot water at three temperature regimes (200C, 400C, 600C) for 5, 10 and 15 minutes and sulphuric acid (H2SO4) at three levels of concentrations (10%, 30%, and 50%)  respectively. Data was subjected to descriptive and inferential statistics (both one and two ways analysis of  variance). Highest germination percentages were recorded in seeds scarified around the circumference, hot water at 600C for 5 min and 50% sulphuric acid for 15 min (36.7%, 53.3% and 50%)    respectively.Circumference scarification, degree of water (200C and 600C) duration (5 and 15 min  respectively) had significant (p<0.05) effect on the seedling height (16.03cm, 13.85 cm and 12.87cm)  respectively. Scarification along the circumference had significant (p<0.05) effect on the fresh and turgid  weights (7.65g and 7.67g) respectively while, 200C and 400C for 5 minutes had significantly (p<0.05) higher  turgid weights (4.97g and 5.40g) respectively.